Break into the Internet! : pick your player, start your quest - Jablonski, Carla; Disney Storybook Artists (Los Angeles : Disney Press, 2018)
A movie tie-in, choose-your-own-adventure story in which readers assume the identity of either Wreck-It-Ralph or Vanellope Von Schweetz and travel through the Internet with Fix-It Felix, Jr., Yesss, and Gene trying to save the Sugar Rush video game and Litwak's Arcade.
Inspired by the motion picture Ralph breaks the internet: wreck-it Ralph 2.
5.5
3-6
Keywords: Video game characters -- Juvenile fiction; Video games -- Juvenile fiction; Friendship -- Juvenile fiction; Internet -- Juvenile fiction; Adventure stories; Video game characters -- Fiction; Video games -- Fiction; Friendship -- Fiction; Internet -- Fiction; Adventure and adventurers -- Fiction; Choose-your-own stories; Action and adventure fiction; Humorous fiction